2014
DOI: 10.1016/j.diii.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Medico-economic study of the management of hepatocellular carcinoma by chemo-embolization

Abstract: This medico-economic analysis demonstrates that the TACE-DEB procedure is fundable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Lastly, TACE is a relatively expensive technique [12] and few studies provide information about cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, TACE is a relatively expensive technique [12] and few studies provide information about cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…An economic study has recently shown that TACE with loaded microspheres was globally financially viable despite the higher basic costs of these devices compared to Lipiodol ® and that a ratio of 1.3 sessions (conventional TACE/TACE with microspheres) would enable the new technique to be funded [37]. In practice, conventional TACE is still widely used [38] and the stability of an idarubicin-Lipiodol ® emulsion which has a release profile for the anticancer agent similar to that of the microspheres could lead to a resurgence in the use of the conventional technique [25].…”
Section: Tace With Microspheresmentioning
confidence: 98%
“…It is routinely used in French economic evaluations to assess hospital production costs. [27][28][29] Finally, cost data from the SHI were used to calculate hospital revenue using DRG tariffs in addition to tariffs for daily supplements and other modifiers. 30…”
Section: Data Sourcesmentioning
confidence: 99%